Culture, leadership, and performance management as drivers of employee work ethic: Evidence from Indonesia Eximbank (LPEI) Jakarta - Subroto, Subroto (Journal of Economics and Business Letters, 2024)
This study investigates whether organizational culture, leadership, and performance management jointly shape employee work ethic in a policy-bank context. Drawing on Lembaga Pembiayaan Ekspor Indonesia’s (LPEI) TRUST cultural code and its competency-based HR architecture, we conducted a cross-sectional survey of Jakarta-based staff and structural-position employees using five-point Likert measures aligned to validated constructs (Competing Values Framework for culture, transformational/contingent-reward behaviors for leadership, continuous-system indicators for performance management, and MWEP facets for work ethic). Instrument screening indicated acceptable validity and reliability (α≈0.81 culture; 0.90 leadership; 0.70 performance management; 0.79 work ethic), consistent with recommended thresholds for organizational measures. Descriptively, respondents reported strong culture, leader behaviors, performance routines, and work-ethic profiles—especially on integrity, time discipline, and diligence—consistent with the theory that values and competencies have been institutionalized in daily operations. Bivariate associations between the three predictors and work ethic were positive but small and not statistically significant at α=0.05, a pattern plausibly explained by restricted variance from high institutional baselines, some indicator attenuation, and single-time-point design. Substantively, the direction of effects supports the theoretical model linking culture, leadership, and continuous performance management to work-ethic behaviors in export-finance settings. We outline actionable refinements—greater role-appropriate delegation, behaviorally anchored PM indicators tied to CBHRM proficiency levels, and unit-level problem-solving forums—and recommend future multi-unit or longitudinal designs (and/or latent-variable models) to recover true effects that current ceiling levels may mask.